Assessment of preference for varied versus constant reinforcers. - Bowman, L G (1997)
One method that has been demonstrated to improve the effectiveness of reinforcement is stimulus (reinforcer) variation (Egel, 1980). Egel found that bar pressing increased and responding occurred more rapidly during varied reinforcement than during constant reinforcement when identical stimuli were used across phases for 10 individuals with autism. The purpose of the current investigation was to assess the preferences of 7 individuals for varied presentation of slightly lower quality stimuli relative to constant access to the highest quality stimulus. Varied presentation was preferred over constant reinforcer presentation with 4 participants, and the opposite was true for 2 participants. One participant did not demonstrate a preference. These results suggest that stimulus variation may allow less preferred reinforcers to compete effectively with a more highly preferred reinforcer for some individuals.